What drives Saudi airstrikes in Yemen? An empirical analysis of the dynamics of coalition airstrikes, Houthi attacks, and the oil market - Dawud Ansari; Mariza Montes de Oca; Helen Schlüter (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Since 2015, Saudi Arabia has led a foreign military intervention against the Houthi movement, which took over major parts of Yemen. The intervention, which manifests mainly in airstrikes, has attracted widespread controversy in media and politics as well as a large body of (qualitative) academic literature discussing its background and ways to escape it. Complementary to these efforts and connecting to the literature on oil and conflict, this study provides unique quantitative insights into what drives the extent of military interaction. We use a vector autoregressive (VAR) model to analyse the interactions between Saudi airstrikes in Yemen, gains of the Houthi movement on Yemeni ground, their attacks on Saudi Arabian soil, and crude oil prices. Our approach builds on high-resolution data from the Yemen Data Project and the Armed Conflict Location and Event Data Project. Our results show not only that the airstrike campaign has been factually impotent to repulse the Houthi movement but also that the movement's expansion in Yemen has not driven Saudi airstrikes. These findings draw both suitability and justification of the intervention further into question. Moreover, although the data fail to show that oil price levels drive the developments, our model identifies oil price volatility as a determinant for the airstrikes. However, the intervention has, in turn, no significant effect on oil markets. Besides adding to the academic discourse on oil and conflict, our results have implications for energy and climate policy: a coordinated transition might not deteriorate regional security, while uncertainty and fluctuations can increase conflict potential.
Keywords: C32; F51; Q34; Q54; 330; Saudi Arabia; Yemen war; VAR model; oil prices; military conflict; regime legitimacy